Modern Radiotherapy and Cardiac Toxicity in Breast Cancer - Giuseppe Carlo Iorio; Valeria Chiofalo; Umberto Ricardi (Clinical and Experimental Obstetrics & Gynecology)
Radiotherapy (RT) is a mainstay of Breast Cancer (BC) patients therapy. Nonetheless, unintended irradiation of the heart and its substructures can result in cardiac toxicity, jeopardizing long-term survivors’ quality of life (QOL). Advances in RT delivery techniques deeply impacted this clinical scenario. Indeed, given the non-negligible burden of cardiotoxicity, modern cardiac sparing approaches have a pivotal role. Nonetheless, further evidence is eagerly awaited regarding patients’ selection, clinical predictors, biological markers, and particularly heart substructures dose-constraints.